Large Shareholders and Independent Director Equity Compensation - Adithipyangkul, Pattarin; Leung, T. (Wiley-Blackwell Publishing Asia, 2016)
This paper investigates the use of equity compensation for independent directors, with a focus on the impact of large shareholders on a company's tendency to use equity compensation to align independent directors’ interests with those of shareholders. Based on data from 215 large Australian listed companies from 2005–2009, our analyses show that the use of equity incentive pay for independent directors is more likely when the aggregate ownership percentage of large shareholders is moderate, when there are multiple large shareholders and when the ownership stakes of large shareholders are more comparable. This paper contributes to the literature by providing new evidence of how various aspects of ownership dispersion affect compensation design for independent directors.